2017
DOI: 10.1002/cctc.201601174
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of Ullmann‐Type C–N Coupling Reactions: Carbonate‐Ligated Copper(III) Intermediates

Abstract: In Ullmann‐type C−N coupling reactions, the involvement of CuIII species has been proposed many times on the basis of the oxidative addition–reductive elimination (OA‐RE) path for these reactions, but actual species could not be traced in experimental studies. In the C−N coupling reactions, carbonate and phosphate were considered widely as bases. In the present study, Cu‐mediated C−N coupling reactions of aryl halides and NuNH (amide and imide) were investigated extensively, and we provide direct spectroscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 58 publications
2
26
1
Order By: Relevance
“…For the formation of 14, L1Cu + (1) is selected as initial species, it reacts with AcNH2 and CO3 2-and can turn in to 14 and 6 respectively (Scheme-III It has good agrrement with our previous studies [12]. Recentlly, it is also reported that deactivaation of catalyst is more significant in fine powdered K2CO3 [15].…”
Section: Generation Of Nucleophile Ligated Inert [Cu(nu) 2 ] -Speciesmentioning
confidence: 69%
See 2 more Smart Citations
“…For the formation of 14, L1Cu + (1) is selected as initial species, it reacts with AcNH2 and CO3 2-and can turn in to 14 and 6 respectively (Scheme-III It has good agrrement with our previous studies [12]. Recentlly, it is also reported that deactivaation of catalyst is more significant in fine powdered K2CO3 [15].…”
Section: Generation Of Nucleophile Ligated Inert [Cu(nu) 2 ] -Speciesmentioning
confidence: 69%
“…It was proposed that benzene forms through trapping of hydrogen from solvent or ligand by phenyl free radical. Cu(II) species can form through free aryl radical formation via outer sphere electron transfer ( ever, these reactions operate through oxidative addition-reductive elimination pathway [12,21]. Calculated free energy barriers for free radical formation are very high (93 kcal/mol).…”
Section: Generation Of Nucleophile Ligated Inert [Cu(nu) 2 ] -Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, applying our knowledge of the Arrhenius equation, in which the energy transmitted by microwaves affects the parameters of pressure, heating and especially time. The reaction time in all C-N couplings could be reduced for the synthesis of anilines when we increase the temperature to 160 • C [76][77][78].…”
Section: Synthetic Methodology Improvements For Aniline Precursorsmentioning
confidence: 99%
“…In this report, we have utilized UV‐Vis, FT‐IR and HRMS techniques to investigate the catalytic process. The UV‐Vis absorption spectrum of the phenol and iodobenzene were monitored separately with successive addition of catalytic substances such as CuI, Cs 2 CO 3 , L1 and finally the second substrate iodobenzene (PhI) to phenol (PhOH) and vice‐versa . The addition of CuI, Cs 2 CO 3 and L1 to the PhOH produced a shoulder around 240 nm in the phenol UV‐Vis absorption spectrum (Figure , (A)), whereas in the case of iodobenzene significant changes were not observed for similar additions (Figure , (B)).…”
Section: Mechanistic Studiesmentioning
confidence: 99%